1993
DOI: 10.1530/jrf.0.0990681
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of day-7 bovine embryos by cytophotometric DNA measurements

Abstract: A Feulgen staining procedure that stains the DNA of individual fixed nuclei stoichiometrically was used to analyse cytophotometrically the incidence of total ploidy and mixoploidy in 28 day-7 bovine embryos that had been fixed after collection ('non-cultured' embryos). The influence of culture on the incidence of chromosome abnormalities was further studied in another group of 24 embryos ('cultured' embryos) by culturing them for 24 h in Whittingham's medium. Of the total 52 embryos studied, two appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Vandaele et al [35] reported that the ratio of the apoptotic index in blastocysts increases at 8 d after IVF. In addition, IVF embryos are known to have reduced developmental viability during the process of IVC because of chromosomal abnormalities and decreased ICM content ratios [29,31]. These type of findings indicate that conventional IVC conditions reduce embryo viability and that the conditions are suboptimal for further embryo development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vandaele et al [35] reported that the ratio of the apoptotic index in blastocysts increases at 8 d after IVF. In addition, IVF embryos are known to have reduced developmental viability during the process of IVC because of chromosomal abnormalities and decreased ICM content ratios [29,31]. These type of findings indicate that conventional IVC conditions reduce embryo viability and that the conditions are suboptimal for further embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…We also know that the developmental speed of bovine preimplantation embryos changes during periods of early cleavage stages, such as pronuclear formation in the first CD and genomic shift from the maternal to embryonic genome in the 3-4th CD [10,11,27,28], and during periods of morphological change, such as compact formation and hatching from zona pellucidae [10,27,29]. Characteristic changes in cell division, such as chromosomal abnormalities [29][30][31] and a difference in the developmental process because of the sex of embryos [32,33], were also found after blastocyst formation. Using VIVO embryos collected from superovulated donors, we previously observed developmentally retarded embryos and embryos with degenerated blastomeres, as described in other similar reports [20][21][22].…”
mentioning
confidence: 99%
“…The most frequent abnormality noted was polyploid cells within diploid embryos resulting in 2n/4n mixoploids although diploid/triploid and diploid/haploid mixoploids were also seen (King and Picard, 1985;King, 1990;Slimane-Bureau and King, 2002). Relatively few entirely polyploid or aneuploid embryos were identified (Dorland et al, 1993). As cytogenetic techniques applied to embryos became more refined as with fluorescent in situ hybridization (FISH), it became possible to assess the chromosomal status of all cells (metaphase and interphase) in individual embryos (Slimane- Bureau and King, 2002).…”
Section: Chromosome Variation In Embryosmentioning
confidence: 99%
“…The incidence of total ploidy and mixoploidy on day 7 bovine embryos, especially mixoploidy, could be better studied by a Feulgen staining procedure measuring the DNA content of the individual nuclei of an embryo, and it was suggested that the presence of hyperdiploid and hypodiplo id nuclei might i ndicate t he f requent occurrence of mitotic segregation failures during mitosis in bovine embryos [44].…”
Section: Embryonic Development To the Blastocyst Stage And Deviation mentioning
confidence: 99%